O ZONEAMENTO MORFOLÓGICO FUNCIONAL DAS CIDADES MÉDIAS MINEIRAS: O EXEMPLO DE BARÃO DE COCAIS - Melina Amoni Silveira Alves; Alexandre Magno Alves Diniz (Sociedade & Natureza)
The present work analyses the morpho-functional organization of Barão de Cocais (MG), based onAmorim Filho´s (2005) model. This model identifies intra-urban spatial organization, identifyingfunctions and relationships the city establishes with its areas of influence. The fundamental reason forthis study is the realization that Barão de Cocais is a clear example of an Emerging Urban Center,result of economic development processes. In addition to it, the city has experienced over the lastdecades intense economic growth, undergoing significant environmental and social chances, which, inturn, influence the intra-urban (re) organization. Morpho-functional studies of mid-sized cities presentnew perspectives and Geography enjoys a privileged position with this regard. This work touchesvarious urban aspects of Barão de Cocais, bringing to life multiple geographical facets.